2008
DOI: 10.1159/000181152
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Polymorphisms Are Associated Both with Increased and Decreased Longevity

Abstract: Previous work compared frequency of longevity-associated polymorphisms (LAPS) in long-lived individuals and in controls from the general population (primarily in Europe and Japan), suggesting the polymorphisms are responsible for unusual longevity. However, individuals from the general population are not the control group for long-lived subjects because both were born in different periods. We report results of a project which collected mtDNA from living subjects in Costa Rica, and traced back their maternal ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Both strands of the HVR-I were sequenced. In addition, seven binary PCR-restriction fragment length polymorphisms were typed, known to be specific to maternal lineages within America, Europe, and Africa, in order to help define the haplogroups, namely 1663HaeIII, 13592HpaI, 110397AluI, 110871MnlI, 211251 Tsp509I, 113262 AluI, 214766 MseI, and the COII/tRNAlys 9-bp deletion (Castri et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Both strands of the HVR-I were sequenced. In addition, seven binary PCR-restriction fragment length polymorphisms were typed, known to be specific to maternal lineages within America, Europe, and Africa, in order to help define the haplogroups, namely 1663HaeIII, 13592HpaI, 110397AluI, 110871MnlI, 211251 Tsp509I, 113262 AluI, 214766 MseI, and the COII/tRNAlys 9-bp deletion (Castri et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Finally, Castri et al. have found that while mtDNA variants can be linked to both increased and decreased longevity, the time period in which a person was born has a much greater impact on longevity than the presence or absence of a particular polymorphism [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, a study of an Irish population failed to link longevity to any particular mitochondrial haplotype, indicating that factors other than mtDNA polymorphism also may play a role in aging [12]. Finally, Castri et al have found that while mtDNA variants can be linked to both increased and decreased longevity, the time period in which a person was born has a much greater impact on longevity than the presence or absence of a particular polymorphism [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, understanding admixture in this population is essential for disease susceptibility mapping studies, and Costa Rica's population has been extensively studied for psychiatric diseases (Contreras et al 2010;Escamilla et al 2009;Escamilla et al 2007; Walss- Bass et al 2006;Walss-Bass et al 2009), longevity (Castri et al 2011;Castri et al 2009) and other disease studies (Leon et al 1992). …”
mentioning
confidence: 99%